Semiotics in Qur'anic Interpretation: The Application of Semiotic Theory in the Tafsir of Jalalain, Ibn Kathir, and Al-Tabari on QS. An-Nur Verse 35 - Suhemi, Emi (El-Sunan: Journal of Hadith and Religious Studies, 2024)
This study investigates methods of Qur'anic interpretation through a linguistic approach, with a focus on semantics and semiotics—both of which are essential for mufassirs (Qur'anic interpreters) in understanding Arabic. The primary objective is to explore how semiotic concepts are applied in interpreting the word نُور (Nuur, meaning "light") in verse 35 of Surah an-Nur. This research adopts a library-based content analysis with a qualitative descriptive approach. Semiotic theory is employed to examine the tafsir works of Jalalain, Ibn Kathir, Quraish Shihab, and al-Tabari. Semiotics, the study of signs and their meanings, reveals that these mufassirs have applied semiotic principles in their interpretations. In Tafsir Jalalain, Saussure’s semiotic theory is evident in the treatment of نُور, where the signifier represents meanings such as light, guidance, and Islam. In Tafsir Ibn Kathir, Roland Barthes’ semiotics is utilized, highlighting both the denotative and connotative meanings of the word. In Tafsir al-Tabari, Roman Jakobson’s communication model is applied, incorporating elements like sender, receiver, and message. In conclusion, this study demonstrates that semiotic concepts are widely integrated into the interpretative practices of mufassirs in their analysis of Qur'anic verses.